Respostas
respondido por:
5
Boa noite
3x - 5y = -14,(*-1)
-2x - 8y = -2 (*-1)
5y - 3x = 14 (*2)
8y + 2x = 2 (*3)
10y - 6x = 28
24y + 6x = 6
34y = 34
y = 1
5 - 3x = 14
3x = -9
x = -3
S = (-3, 1)
3x - 5y = -14,(*-1)
-2x - 8y = -2 (*-1)
5y - 3x = 14 (*2)
8y + 2x = 2 (*3)
10y - 6x = 28
24y + 6x = 6
34y = 34
y = 1
5 - 3x = 14
3x = -9
x = -3
S = (-3, 1)
GabrielRamosDias:
Vlw
respondido por:
0
Explicação passo-a-passo:
Resolução!!!
{3x -5y =-14
{-2x -8y =-2
{3x -5y =-14(*2)
{-2x -8y =-2(*3)
6x-10y=-28
-6x-24y=-6
-34y=-34
Y=-34/-34
Y=1
-2x-8y=-2
-2x-8*1=-2
-2x-8=-2
-2x=-2+8
-2x=6
X=-6/2
X=-3
S=>{ -3 e 1}
Espero ter ajudado!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás